Genome-wide mapping of DNase I hypersensitive sites in pineapple leaves - Ouyang, Kai; Liang, Qifu; Miao, Li; Zhang, Zhiliang; Li, Zhanjie (Frontiers in Genetics, 2023)
Pineapple [Ananas comosus (L.) Merr.] is the most economically important crop possessing crassulacean acid metabolism (CAM) photosynthesis which has a higher water use efficiency by control of nocturnal opening and diurnal closure of stomata. To provide novel insights into the diel regulatory landscape in pineapple leaves, we performed genome-wide mapping of DNase I hypersensitive sites (DHSs) in pineapple leaves at day (2am) and night (10am) using a simplified DNase-seq method. As a result, totally 33340 and 28753 DHSs were found in green-tip tissue, and 29597 and 40068 were identified in white-base tissue at 2am and 10am, respectively. We observed that majority of the pineapple genes occupied less than two DHSs with length shorter than 1 kb, and the promotor DHSs showed a proximal trend to the transcription start site (>77% promotor DHSs within 1 kb). In addition, more intergenic DHSs were identified around transcription factors or transcription co-regulators (TFs/TCs) than other functional genes, indicating complex regulatory contexts around TFs/TCs. Through combined analysis of tissue preferential DHSs and genes, we respectively found 839 and 888 coordinately changed genes in green-tip at 2am and 10am (AcG2 and AcG10). Furthermore, AcG2-specific, AcG10-specific and common accessible DHSs were dissected from the total photosynthetic preferential DHSs, and the regulatory networks indicated dynamic regulations with multiple cis-regulatory elements occurred to genes preferentially expressed in photosynthetic tissues. Interestingly, binding motifs of several cycling TFs were identified in the DHSs of key CAM genes, revealing a circadian regulation to CAM coordinately diurnal expression. Our results provide a chromatin regulatory landscape in pineapple leaves during the day and night. This will provide important information to assist with deciphering the circadian regulation of CAM photosynthesis.